Turkey : Financial Sector Assessment Program-Detailed Assessment of Observance of the IAIS Insurance Core Principles. (IMF Staff Country Reports; Country Report ;, 2017)
This paper presents an assessment of the observance of IAIS (International Association of Insurance Supervisors) insurance core principles in Turkey. During the last five years, the government of Turkey has made a significant effort to improve regulation and supervision of insurance and to improve adherence to international standards. The efficiency of information reporting, insurer monitoring, and supervision has greatly increased. Solvency tests have been strengthened. Reserving and investment practices have been improved. Improvements have been made in international cooperation and information exchange. However, major regulatory and supervisory challenges remain for Turkey to increase confidence in the sector and benefit from its continued growth.